Clinical, Laboratory, and Histopathological Evaluation of 493 Patients Who Underwent Endoscopic Biopsy with a Presumptive Diagnosis of Celiac Disease: Association with Autoimmune Diseases - Elife Kımıloğlu,; Ahenk Karagülle,; Meryem Keçeciler,; Eylem Akbay Karatay,; Deniz Koç, (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Celiac disease is an immunological reaction provoked by gluten digestion in genetically vulnerable individuals in response to unknown environmental factors. It affects 0.7% of the world’s population and occurs at a rate of 1% in most nations. We aimed to assess the clinical, laboratory, and histopathological characteristics of patients with a presumable diagnosis of celiac disease and to investigate the coexistence of autoimmune disorders.Materials and Methods: In this retrospective study, data were gathered from the medical files of a total of 493 individuals with a preliminary diagnosis of celiac disease who underwent endoscopic biopsies. Analysis was carried out for clinical, biochemical, and histological results, as well as the presence of autoimmune disease.Results: Per the results of serological tests used in the diagnosis of celiac disease in this series, gliadin IgA and IgG positivities were found in 33.7% (n = 54/160) and 39.4% (n = 69/175) of patients; endomysium IgA and IgG positivities were detected in 37% (n = 88/238) and 18% (n = 30/167) of patients, while tissue transglutaminase IgA and IgG positivities were detected in 47.3% (n = 115/243) and 16.3% (n = 15/92) of patients, respectively. The incidence of patients with a CD3 level of ≥30% was 69.1% in 152 patients whose CD3 levels were tested.Conclusion: The general public and healthcare professionals need to be more aware of the prevalence and many signs of celiac disease. There is still a need to conduct the necessary research in this area. By boosting awareness, early diagnosis, and diet, it will be possible to prevent symptoms and negative consequences.Cite this article as: Kımıloğlu E, Karagülle A, Keçeciler M, Akbay Karatay E, Koç D. Clinical, laboratory, and histopathological evaluation of 493 patients who underwent endoscopic biopsy with a presumptive diagnosis of celiac disease: Association with autoimmune diseases. Turk J Gastroenterol. 2023;34(7):681-690.